Nottinghamshire Miners' Association (leaflet) - Bayliss, W.; Coleman, Val
015b_0026_001 Nottinghamshire Miners' Association Affiliated to the Mine Workers' Federation of Great Britain December, 1936. FELLOW CITIZENS, Trades Unions functioning in a legitimate manner make a valuable contribution towards the management of the present social order, and are accepted by all broad-minded people as the instrument of collective expression for the workers generally. The miners of Nottinghamshire have been denied the right of collective bargaining for a period of ten years, as the result of the coal-owners' action in fostering a form of " company unionism " which precludes the operation of " Free Trades Unions." The effect of this is that the miners in this county have no means of discussing matters which adversely affect them only through channels which will never give them satisfaction. At Harworth Colliery, on November 4th, 1936, a ballot vote was taken, under public supervision on the public highway, to ascertain the views of the men as to which organisation they desired to be attached to - The Miners' Federation or the Spencer Union. 1,175 voted for the Notts. Miners' Association and the M.F.G.B. whilst only 145 voted for the Spencer or the Company Union. The management of the colliery totally ignored the wishes of the men, and endeavoured to impose membership of Spencer's Union as a condition of employment, and asked many of the men to sign a form authorising contributions to be deducted from wages. A very large number of the men rightly refused to sign away their freedom, and consequently were not allowed to work! we consider they were locked out and we advised the rest of the men to give notice to terminate contracts, which has been done. The Miners' Federation endorsing this action and giving full financial support. This effort to re-establish the right to choose their own union must be appreciated by all freedom lovers, we are therefore appealing for you to show your appreciation in a practical manner by sending as large a contribution as possible to augment the funds so very generously created by the miners from every part of the British coalfield. Contributions to the Harworth "Fight for Freedom Fund" will be gratefully received by the Financial Secretary of the Notts. Miners' Association. Miners' Offices, Nottingham Road, Old Basford, Nottingham. Signed, VAL. COLEMAN, General Secretary. ALD. W. BAYLISS, J.P., Financial Secretary 292/946/15b/26